Child Abuse: Dr. Karagianis and Dr. Nesbit - Memorial University of Newfoundland. Educational Television Centre
Drs. Wayne Nesbit and Leslie Karagianis discuss the emotional abuse of children. Some things discussed are: what constitutes emotional abuse, who can emotionally abuse a child, what to look for to identify an emotionally abused child. Vignettes are shown to depict an emotionally abused child in the classroom and parents discussing their physically disabled child going to a summer camp which becomes an emotionally abusive situation.